Characterization of stem cell-derived vesicles for drug delivery - Koulenti, Maria (Department of Electrical Engineering and Computer Engineering and Informatics,Faculty of Engineering and Technology, Cyprus University of Technology, 2018)
Cancer is among the leading causes of death worldwide. Uncontrollable or abnormal cell proliferation is one of the main characteristics of cancer, leading to tumor formation. Conventional cancer therapies not only affect the cancer cells but also influence the healthy cells. Thus, the development of more efficient drug delivery systems for targeted cancer therapy will overcome the consequences of current treatments, by destroying only the malignant cells. This study concerns the Wharton's Jelly Mesenchymal Stem Cell (WJMSC)-derived vesicles as drug delivery systems, due to their unique properties such as selectively homing in sites of inflammation and tumors and selectively delivering of therapeutic miRNAs to target cells, and thus regulate targeted gene expression and cellular function. The aim of the study is to characterize the WJMSC-derived vesicles (Extracellular vesicles: particles including exosomes (<100nm) and Microparticles: (O.lpm-lpm)), elucidating their precise size and concentration, in order to be used for future in vitro and in vivo studies. MSC-derived vesicles were separated in size groups via Exclusion Chromatography Separation qEV columns, in order to check in subsequent studies whether an infiltration will selectively occur in an organ and to check, what the size range of the vesicles that influence this infiltration, will be. Although, the small size and the heterogeneity in size and composition of these vesicles make their quantification challenging, samples and fractions of these vesicles were characterized, in terms of size and concentration, via Tunable Resistive Pulse Particle (TRPS) analysis. Concentration measurements of vesicles are crucial, in order to check in subsequent studies which vesicles' concentration will result in the successful reduction of the cancer tumors. Furthermore, samples and fractions of the vesicles were analyzed via Scanning Electron Microscopy (SEM), in order to verify the presence of vesicles in the samples and to check their morphology and size, in order to validate the results of TRPS analysis. Finally, the samples and fractions were analyzed, in terms of protein, RNA, miRNA concentration using Spectrophotometer, in order to check whether measured vesicles were active and biological vesicles and not fragments of inorganic material. The results based on TRPS analysis indicated that the size separation using qEV size exclusion columns did not separate these vesicles in size groups, under specific conditions. SEM analysis in the fractions showed large multi-shaped particulates with crystal structures, which they had a distinctly different appearance from biological particles, compared to the vesicles that were found in the samples, in which the separation method was not applied. Protein, RNA and miRNA analysis showed very small concentrations of protein, RNA and miRNA in the fractions, suggesting non biological particles or very low vesicle concentration, compared to the high concentration in the samples, in which the separation method was not applied. The qNano instrument achieved successful measurements of the size and concentration of the vesicles, showing good repeatability. The particle-by-particle measurement of the size and concentration of the WJMSC- derived vesicles was achieved; however the separation and characterization methods need to be standardized and validated, in order to have accurate and validated results when these measurements will be applied for preclinical and clinical use.
Keywords: TRPS; qNano; Size Exclusion Chromatography; Mesenchymal Stem Cells; Microparticles; Extracellular Vesicles; Wharton's jelly